Eﬀects of host plants and substrate colour on the oviposition behaviour of green lacewing Apertochrysa astur (Banks) (Neuroptera: Chrysopidae) - Nelson, S. Jeyarajan; Remoniya, X. (Journal of Plantation Crops, 2023)
The Green lacewing, Apertochrysa astur also known as “aphid lion” is an eﬃcient predator of various soft bodied insect pests. A laboratory experiment was conducted in Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to observe the preference of A. Astur on their oviposition behaviour. Egg receiving sheets were pasted with black, amber, ash, parrot green, violet, red, light green, pink, blue, fluorescent yellow, sky blue, yellow, orange and white coloured papers. Among all the colours, females of A. astur preferred black colour as a substrate for laying eggs (19.6 per cent of eggs) followed by orange colour substrate (15.5per cent) while white was the least preferred colour (4.0 % eggs). Among the host plants examined, maximum number of eggs was laid in the coconut leaves infested with the invasive whiteflies followed by custard apple and banana. Therefore, whitefly infested coconut leaves and the black coloured substrate can be used in the mass production of A. astur in the laboratory.